The Effect of Using the Picture and Picture Method on the Beginning Reading Ability of Grade III Students in Indonesian Language Subjects in Elementary School: Pengaruh Penggunaan Metode Gambar dan Gambar Terhadap Kemampuan Membaca Permulaan Siswa Kelas III pada Mata Pelajaran Bahasa Indonesia di Sekolah Dasar - Setyawati, Isnaini; Liansari, Vevy (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine whether there is a picture and picture method on the initial reading ability of third grade students in Indonesian language subjects in elementary schools. This type of research is pre-experimental design. The sample is 22 students. The instrument is about the form of a description. The results obtained from the pretest data obtained, that the average value of initial reading ability is 54.6 and the results of posttest data obtained, that the average value of initial reading ability of third grade students at SDN Pejangungan is 75.36. From the statistical analysis of the t test, it was found that the result of T arithmetic was 20.6 and T table was 2.080, it was proven that if T arithmetic > T table, it could be concluded that there was an effect of the independent variable (X), on the dependent variable (Y) or the hypothesis was accepted. This is evidenced by the effect of the picture and picture method on the early reading ability of third graders at SDN Pejangungan.